A perfectly messed-up story [book with audioplayer] - McDonnell, Patrick, 1956- ([Library Ideas, LLC], 2018)
Little Louie's story keeps getting messed up, and he's not happy about it! What's the point of telling his tale if he can't tell it perfectly? But when he stops and takes a deep breath, he realizes that everything is actually just fine, and his story is a good one-imperfections and all.